2022
DOI: 10.3390/foods11071057
|View full text |Cite
|
Sign up to set email alerts
|

Widely Targeted Metabolomics Analysis Reveals the Differences of Nonvolatile Compounds in Oolong Tea in Different Production Areas

Abstract: The flavor differences in Oolong tea from different producing areas are caused by its complex differential compounds. In this study, representative samples of Oolong tea from four countries were collected, and their differential nonvolatile compounds were analyzed by a combination of widely targeted metabolomics, chemometrics, and quantitative taste evaluation. A total of 801 nonvolatile compounds were detected, which could be divided into 16 categories. We found that the difference in these compounds’ content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Here, we employed OPLS-DA, as it is an effective method for screening DEMs [ 10 ]. In order to screen the DEMs of tea plants of different ages from the two cultivars, OPLS-DA analysis was performed with all of the relevant metabolites as variables.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, we employed OPLS-DA, as it is an effective method for screening DEMs [ 10 ]. In order to screen the DEMs of tea plants of different ages from the two cultivars, OPLS-DA analysis was performed with all of the relevant metabolites as variables.…”
Section: Resultsmentioning
confidence: 99%
“…Cross-validation indicated that the interpretation degree of the two models was high, and there was no fitting phenomenon ( Figure S2 ). Their DEMs were screened according to the principles of VIP > 1.00 and p < 0.05 [ 10 ] ( Table S3 ). There were 92 DEMs shared between WL-7 and WL-40, among which 50 metabolites were upregulated and 42 metabolites were downregulated in WL-40 ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations